Journal of Large Mammal Species Diversity in Ujung Kulon National Park (A Preliminary Study of Development Research in Vertebrate Sub-Concept) - Enggar Utari; Indria Wahyuni; Rizka Nur Fadhilah (Universitas Tidar, 2022)
This study aims to determine the diversity of large mammal species in Ujung Kulon National Park. This research was conducted at 4 research stations, namely Peucang Island, Handeuleum Island, Cigenter, and Cidaon in March-June 2021. The data collection method used was a line transect combined with the Variable Circular-Plot (VCP) method with a random data collection technique. direct and indirect observation. The results showed that there were 6 species of large mammals found, namely Macaca fasicularis, Cervus timorensis, Bos javanicus, Sus scrofa vitalus, Rhinoceros sondaicus, and Cuon alpinus. The index value for the diversity of species of large mammals is 1.50 which is included in the medium category, the index value for species richness of large mammals is 0.93 which is included in the low category, and the index value for the evenness of species for large mammals is 0.84 which is included in the medium category. The results of this study will be implemented as an initial research study on the development of vertebrate subconcepts development research.